The Role of Rural Cities' Festivals in the Development of Regions - Katalin Ásvanyi; Melinda Jászberényi (DETUROPE)
Festival tourism is a dynamically developing area of tourism which is supported by the growing number of festival tourists and by the strengthening of traveling motivations to festivals. The festivals have become very important attractions of the cities and regions. The number of rural cities’ festivals which are mainly for the local communities, is growing by leaps and bounds, but the number of festivals specifically for tourists is also high. The tourist impacts of festivals could be analyzed at economical, physical, environmental, social and cultural levels, but the socio-cultural impact is an under-researched field. In this study we analyzed rural cities’ festivals. We evaluated them on the basis of information available on their websites according to a predetermined criterion. The points of interest from the aspect of regional impacts were highlighted. Our research aims to show the best practices, so how the festival could attribute to the development of the regions.